Genesis, Isaiah, and Psalms : a festschrift to honour Professor John Emerton for his eightieth birthday - Emerton, John Adney.; Dell, Katharine J. 1961-; Davies, Graham I.; Koh, Y. V. (Vetus Testamentum, Supplements, 2010)
Genesis, Isaiah and Psalms are three key texts in the Hebrew Bible and represent the lifelong interests of Professor John Emerton, Emeritus Regius Professor of Hebrew in the University of Cambridge, for whom this volume is written on the occasion of his eightieth birthday. The contributors have all enjoyed academic relationships with John over the years and represent a truly international group. The contributions include comparison of biblical texts with ancient Near Eastern counterparts and evaluation of them in the light of archaeology. They include intertextual work on a literary level, and traditional literary-historical approaches to texts. Many move beyond the Hebrew Bible itself to consider other texts and versions or to draw out interpretations of texts by scholars ancient and modern - and even by novelists. The result is a refreshing group of articles that indicate the broad range of approaches that characterize the discipline of Old Testament study in the present day.